41.7k views
5 votes
F=f (1-v/s) change the subject of the formula into v

1 Answer

6 votes
Changing the subject of the formula into v means expressing v in terms of the other given variables. So given the original equation, as shown below, we can rearrange it so that we have v isolated on one side.


F = f(1 - (v)/(s))

(F)/(f) = 1 - (v)/(s)

(v)/(s) = 1 - (F)/(f)

To isolate v, we can just multiply s to both sides and come up with the final equation below.


v = s(1 - (F)/(f))

Thus, we have v = s(1 - F/f) with v as the subject of the formula.

Answer: v = s(1 - F/f)
User Arch
by
5.6k points